Upaya Meningkatkan Minat Belajar Siswa Melalui Model Pembelajaran Project Based Learning pada Pembelajaran IPAS Kelas VA SDN 03 Bengkayang - Barumanan, Yora Suspita; Silvester, Silvester (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
Based on initial observations, students were less involved in discussions, rarely asked questions, and did not show enthusiasm for science learning. This affects student learning outcomes, which are below the KKM standard. Therefore, an innovative learning model is needed, such as Project-Based Learning (PjBL), which allows students to learn through projects that are relevant to real life. The type of research used is Classroom Action Research (CAR); the research was conducted on grade V students of SDN 03 Bengkayang. The data collection technique uses four main stages in each cycle: planning, action, observation, and reflection. The data analysis technique uses descriptive statistics by comparing learning outcomes between cycles. Based on the results of the research that has been carried out, it can be concluded that there is an increase in student interest in learning after following the learning implementation process using the PjBL model. In cycle I, the highest frequency is in the interest category, and in cycle II, it is in the very interested category. Furthermore, the percentage of interest based on the N-Gain calculation in cycle I can be seen from the highest frequency at 78.1%, entering the effective category; in cycle II, it reaches a percentage of 83.24%, entering the effective category